A modified Deadbeat Current Controller for field oriented induction motor drives - Le Nam Duong; Vu Hoang Phuong; Nguyen van Lien; Tran Trong Minh (My University, 2021)
A modified Deadbeat Current Controller for field oriented induction motor drives
Keywords: Điều khiển Deadbeat; Truyền động động cơ; Induction motor